Variables Affecting Eligible Women in Poor Households to Smoke in Indonesia 2017 - Maghfira Ramadhani; Risni Julaeni Yuhan (Politeknik Statistika STIS, 2021)
Smoking is one of public health threats. Cigarette consumption does not only impact on a person's declining health but also social behavior. Smoking behavior in women, especially eligible women (15-49 years old) threatens women’s reproductive health and the condition of the fetus in the womb during pregnant, which may get worse in poor households. Aside from that, cigarette consumption in Indonesia occupies the second position in food consumption with a portion of 12.17 percent. Therefore, the purpose of this study is to examine the variables that affect eligible women in poor households to smoke in Indonesia. The sources of the research data are the 2017 Indonesia Demographic and Health Survey (2017 IDHS) with the Household and Eligible women questionnaires. The method of analysis used descriptive analysis and inferential analysis with binary logistic regression method in rare event with the firthlogit model. The results of the study show that eligible women in poor households in Indonesia would have a tendency to smoke when they live in urban areas, are more mature in age, their highest educational level is lower than junior high school, work, never access mass media, have partner who do not work and have a big number of household members.